Tanah sebagai Ibu, Alam sebagai Penciptaan: Sintesis Ekoteologi Kontekstual Papua di Tengah Krisis Deforestasi Akibat Ekspansi Kelapa Sawit - Benyamin Dadi Ratu Mofu; Amelia Waimuri; Kristensia Notanubun (Universitas Darul Ulum, 2026)
Oil palm expansion in Papua has deepened the deforestation crisis and presents problems that are not only ecological, but also social, cultural, and theological because they are related to changes in indigenous peoples' relations to land, forests, and sources of life. This research aims to formulate a synthesis of Papuan contextual ecotheology by placing land as a relational living space and nature as a creation that must be read in the context of contemporary ecological crises. The research uses a Systematic Literature Review (SLR) approach based on secondary data from open-access scientific literature relevant to the themes of deforestation, oil palm expansion, indigenous Papuans, relational cosmology, and contextual ecotheology. The analysis process was conducted through literature selection, thematic mapping, and narrative synthesis to identify key patterns of findings. The results show that deforestation due to oil palm expansion in Papua cannot be understood solely as land cover change, but rather as a relational crisis that disrupts indigenous peoples' relationships with land, sago, forests, food, and the wider web of life. This synthesis also shows that Papuan contextual ecotheology needs to be built by integrating creation theology, ecological justice, and local ecological knowledge in order to be able to respond to the reality of extractivism more sensitively and transformatively. This article contributes to the development of ecotheological studies in Indonesia by offering a conceptual framework that places Papua as an important locus for the formation of a theology that is contextual, ecological, and in favor of the dignity of indigenous peoples.